Milli meter Wave MIMO-OFDMA Scheme with MMSE-based VEMF in 6G Wireless Technology (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Millimetre Wave (MmWave) massive multiple-input multiple-output (MmWave-massive MIMO) has developed as beneficial for gigabit-per-second data broadcast into 6G digitized wireless technology. The collection of low-rate and energyefficient (EE) types of machinery, low power consumptions, multi-bit quantized massive MIMO-Orthogonal Frequency Division Multiplexing Access (OFDMA) structure have been planned for the receiver manner. The main concentration effort is the minimization of a state-of-the-art pilot-symbol quantized (PSQ) massive MIMO-OFDMA system (m-MIMO-OFDM-S). Accordingly, in this analysis, by minimizing many advantages of the Variational Estimated Message Fleeting (VEMF) algorithm. A modified low complexity manner VEMF algorithm is invented for the utilization of the ASQ-m-MIMO-OFDM-S structure. Hence, two new modules improve the energy efficiency and spectrum efficiency for wireless smart 6G technology of pilot bits allocation process for MmWave connections of the hybrid MIMO-OFDM receiver structural design. Several technologies such as massive MIMO-OFDMA, 3GPP & 4G& 5G technology, the device-to-device communication (D2D), GREEN communication have increasingly important consideration in assisting spectrum consumption along with power consumption during simulations. The proposed VEMF algorithm has achieved higher capacity, sum rate, Energy Efficiency (EE), and throughput for the receiver section. Finally, we present a greater number of user's data transmissions MmWavemassive-MIMO-OFDMA system.